2020
DOI: 10.7717/peerj.9374
|View full text |Cite
|
Sign up to set email alerts
|

Trophic degradation predispositions and intensity in a high-flow, silted reservoir

Abstract: The objective of the work was to demonstrate the relationship between the natural environmental characteristics of a reservoir and its catchment and severity of trophic degradation. The shallow, highly-silted Rzeszów Reservoir (SE Poland) was the object of study. The impact on degradation of internal supply from accumulated bottom sediments was also assessed, using water and sediment sampled in 2013 and 2014. A high value for trophic state was identified for the reservoir on the basis of TSI indexes, while ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Wang et al [11] reported that both water temperature (25.3 • C in July) and pH (8.00-8.73 pH) significantly influenced the rate of phosphorus release from the sediment, but the effect of water temperature was more significant. In addition, Bartoszek et al [15] noted that the water in the reservoir does not have to be alkaline. As further emphasized by Wang et al [11], acid-base conditions favored the release of phosphorus from sediments, whereas the neutral environment did not.…”
Section: Summary Statistics Of Water Quality Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [11] reported that both water temperature (25.3 • C in July) and pH (8.00-8.73 pH) significantly influenced the rate of phosphorus release from the sediment, but the effect of water temperature was more significant. In addition, Bartoszek et al [15] noted that the water in the reservoir does not have to be alkaline. As further emphasized by Wang et al [11], acid-base conditions favored the release of phosphorus from sediments, whereas the neutral environment did not.…”
Section: Summary Statistics Of Water Quality Parametersmentioning
confidence: 99%
“…In many cases, dam construction results in the retention of the phosphorus fraction [10,11] and nitrogen fraction in reservoir sediments [12,13]. However, due to seasonal changes, in the summer, the reservoir sediments may act as a source of surface water pollution [12,14,15]. In addition, high water pollution is observed during dry periods and intensive rainfall [16].…”
Section: Introductionmentioning
confidence: 99%
“…Rainwater may be contaminated with microorganisms already at the stage of precipitation formation, during the runoff from the surface from which it is collected or at rainwater harvesting systems [19].…”
Section: Introductionmentioning
confidence: 99%
“…Brodie [19] in a study reported that E. coli and other pathogens can enter roofharvested rainwater through aerosol deposition, tree litter, and animal faecal matter. Rainwater may be contaminated with microorganisms already at the stage of precipitation formation, during the runoff from the surface from which it is collected or at rainwater harvesting systems [20]. Thus, this could have influenced the coliforms and other microorganisms in the water samples.…”
Section: Discussionmentioning
confidence: 99%